Parental Preferences and Selective Abortion: A Commentary on Roe v. Wade, Doe v. Bolton, and the Shape of Things to Come - Richard Delgado; Judith Droz Keyes (Washington University Law Quarterly, 1974)
One question not addressed by the Supreme Court in Roe or its companion case, Doe v. Bolton, is whether there are other maternal interests or detriments; nor did the Court consider whether, if there are additional interests, they would prove sufficiently compelling to override countervailing state interests. In particular, the Court did not consider whether a decision to abort based on advance knowledge of certain characteristics of the fetus would also be protected by the mother’s right to privacy. The opinions were simply silent on this issue, and the novelty of the questions raised by selective abortion, as well as the obvious implications of this practice for genetic engineering, make a legal and constitutional inquiry timely and important. In addition to providing an advance view of some of the dilemmas that more sophisticated methods of human genetic engineering will pose ten or twenty years hence, analysis of selective abortion can provide new insight into the dynamics of the recent abortion decisions and their implications for the debate concerning the beginnings of human life.
Keywords: Abortion; Roe v. Wade 410 U.S. 113 (1973); Doe v. Bolton; Selective abortion